Comparative Mercury Removal by Four Aquatic Macrophytes from ASGM-Contaminated Liquid Waste - Nur Rismawati; Hamidah Hamidah; Abdullah Rahman Zain (Journal of Public Health and Pharmacy, 2026)
Introduction: Artisanal and small-scale gold mining (ASGM) is a major source of mercury contamination in aquatic environments, threatening ecosystems and human health. Conventional remediation is often costly and difficult to apply in resource-limited mining areas. Phytoremediation using aquatic macrophytes offers a low-cost alternative. This study compared observed water-phase mercury removal by Ipomoea aquatica, Pistia stratiotes, Nymphaea spp., and Eichhornia crassipes under standardized bench-scale laboratory conditions. Methodology: ASGM liquid waste with an initial dissolved mercury concentration of 0.00448 mg/L was used. Each species was tested in triplicate over a 14-day exposure period, with water samples analyzed on Day 0, Day 9, and Day 14. Mercury concentrations were measured using Atomic Absorption Spectrophotometry, and removal effectiveness was calculated as percentage reduction from baseline. Because biomass-normalized uptake, plant tissue mercury accumulation, and abiotic controls were not included, findings are interpreted as plant-associated water-phase reductions rather than definitive evidence of uptake mechanisms. Results: All species substantially reduced dissolved mercury, with clear interspecies variation. By Day 14, water hyacinth reduced mercury to 0.00003–0.00004 mg/L, corresponding to 99.11–99.33% removal. Lotus showed comparable performance, achieving 98.21–98.44% removal. Water spinach produced intermediate reductions of 85.04–94.42%, with an approximate mean of 89.17%, while water lettuce showed the lowest removal range of 83.71–86.38%, with an approximate mean of 84.89%. Reductions were evident by Day 9 and greatest by Day 14. Mechanistic interpretations related to root morphology, biomass, rhizosphere processes, or internal translocation should remain cautious because these parameters were not directly measured. Conclusion: Aquatic macrophytes can substantially reduce dissolved mercury in ASGM-contaminated liquid waste under bench-scale conditions. Water hyacinth showed the highest observed removal, followed closely by lotus. Field application requires ecological containment, safe biomass disposal, abiotic control assessment, effluent characterization, and further tissue-based uptake studies.